ChemInform Abstract: Total Synthesis of (.+‐.)‐Paroxetine by Diastereoconvergent Cobalt‐Catalyzed Arylation. Issue 7 (29th January 2015) - Despiau, Carole F.; Dominey, Andrew P.; Harrowven, David C.; Linclau, Bruno
Abstract A diastereoselective total synthesis of the antidepressant paroxetine is described.